ETIKA BERBHINEKA: BELAJAR MEMBANGUN KESADARAN MULTIKULTURALISME DARI NABI DAN PARA WALI - Fahim Khasani (LP2M IAIN Tulungagung, 2021)
The problem of multiculturalism is the problem of our civilization. Indonesia with all its differences and cultural richness is one of the countries that has the potential for horizontal conflict. The efforts to unite and maintain unity must be three steps ahead of the threat of disintegration. The disruption era that is completely unpredictable and hoaxes and hate speech on social media makes it difficult to maintain security and maintain a conducive, harmonious and peaceful situation. Hostile with the others is not tradition of Nusantara people. Our tradition is a dialogue as well as strengthening the harmony of every difference. In this case, the Prophet Muhammad and the Walisongo have set a good example of living side by side with different communities. This article will discuss the strategies of the Walisongo in dialogue between religion and culture, as well as the strategy of the Prophet Mohammed in managing differences and building harmony in a pluralistic society. The results of the study conclude that to build a nation that is baldatun thayyibah wa Rabbun ghafur, it is necessary to have a society that is not only saleh ritual, but also saleh sosial and saleh kultural.